The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1115/1.4046482
|View full text |Cite
|
Sign up to set email alerts
|

Improved Inkjet-Printed Pattern Fidelity: Suppressing Bulges by Segmented and Symmetric Drop Placement

Abstract: Inkjet printing is a promising technique for printed micro-electronics due to low cost, customizability and compatibility with large-area, flexible substrates. However, printed line shapes can suffer from bulges at the start of lines and at corner points in 2D line patterns. The printed pattern can be multiple times wider than the designed linewidth. This can severely impact manufacturing accuracy and achievable circuit density. Bulging can be difficult to prevent without changing the ink-substrate-system, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…All of these ink properties affect the jetting and the pattern formation on the substrate. Pattern formation on the substrate can be further manipulated by changing the properties of the substrate and the spacing and order in which drops are deposited [10][11][12][13][14][15][16][17]. Here, we will focus on the ejection of drops from the nozzle, which is the first step in the inkjet process.…”
Section: Introductionmentioning
confidence: 99%
“…All of these ink properties affect the jetting and the pattern formation on the substrate. Pattern formation on the substrate can be further manipulated by changing the properties of the substrate and the spacing and order in which drops are deposited [10][11][12][13][14][15][16][17]. Here, we will focus on the ejection of drops from the nozzle, which is the first step in the inkjet process.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the next segment starts with the fourth drop placed at a distance of (DSp + 2CDSp) relative to the center of the first segment (the third drop), leaving 2CDSp of vacant space between two segments for a connecting drop to be filled in after all the segments have been printed. Previous work has experimentally shown that CDSp should be smaller than DSP, and the optimum CDSp varies between 0.6 and 0.95 times DSp for different substrate and ink combinations [20]. Here, the symmetric printing process is implemented for arbitrary patterns using a vision pipeline shown in figure 6(b).…”
Section: Symmetric Vector Sequence Generationmentioning
confidence: 99%
“…Following the printing of the outer two drops of each segment, the central drop is printed and does not experience a pressure gradient due to the symmetry of the segment. Subsequently, the three-drop segments are joined with a connecting drop while maintaining pressure equilibrium on either side of the pattern [20]. Figure 6(a) compares the raster and symmetric drop ordering methodologies.…”
Section: Symmetric Vector Sequence Generationmentioning
confidence: 99%
See 2 more Smart Citations